Pandangan Islam terhadap Sosial Kemasyarakatan Parmalim - Nst, Fachrurrozi; Harahap, Indra; Syahrin, Abu (ANWARUL, 2023)
Malim is the original religion of the Batak Land. As Adam and Eve are believed to be the first human beings in Islam or Christianity, the story of Raja Ihat and Boru and their descendants is part of Malim's teachings and beliefs. The life of the Parmalim people in the Toba Batak regarding their worship only believes in one god who continues the ancient religious system that was first adopted by the Toba Batak people long before the arrival of Protestantism, Islam and Catholicism. They perform worship rituals every Saturday called Maarari Saturday. Their place of worship is called Bale Persantian Ginomongan Ni Bale Pasogit Partonggoan. The method used in this thesis is a set of knowledge about the systematic and sociological steps of searching data for the problem in question to be processed, analyzed, drawn conclusions and found a way to solve it. This thesis explores data from two sources, namely primary and secondary. The primary data are the Bible and the Koran, while the secondary data are interviews, articles, books, documents and websites. The results of this study want to know the social views of the Parmalim community. Each religion has its own theological basis for claiming its own truth. But at the same time, all religions also have theological basis for stating that only God and Revelation. While the human who conveys religious teachings is the one who gives the interpretation. Therefore, human interpretation of revelation becomes a truth that is not absolute, and remains relative or relative along with its limitations as a human being. With that spirit and attitude then the basics of religious harmony and harmony can be pursued and realized.